Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1200/jco.2016.67.4184
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Tyrosine Kinase Inhibitor Initiation and Adherence Among Medicare Beneficiaries With Chronic Myeloid Leukemia

Abstract: There is substantial concern surrounding affordability of orally administered anticancer therapies, particularly for Medicare beneficiaries. We examined rates of initiation and adherence to tyrosine kinase inhibitors (TKIs) among Medicare beneficiaries with chronic myeloid leukemia (CML) with and without cost-sharing subsidies. We selected TKIs given their effectiveness and strong indication for use among patients diagnosed with CML. Patients and MethodsUsing SEER-Medicare data, we identified individuals diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 32 publications
2
111
1
Order By: Relevance
“…24, 25 In addition, given the chronic nature of CML treatment, expenses associated with monitoring and follow-up can limit adherence. 22, 26 These factors may have contributed to the poor outcomes seen both among the nonelderly uninsured population, and the insured patients over age 65 in this analysis, many of whom would have Medicare insurance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…24, 25 In addition, given the chronic nature of CML treatment, expenses associated with monitoring and follow-up can limit adherence. 22, 26 These factors may have contributed to the poor outcomes seen both among the nonelderly uninsured population, and the insured patients over age 65 in this analysis, many of whom would have Medicare insurance.…”
Section: Discussionmentioning
confidence: 97%
“…However, these programs may have restrictions that exclude certain populations, including elderly patients on Medicare plans and undocumented immigrants. Indeed, previous research has identified cost-sharing as a potential barrier to TKI initiation and adherence among CML patients on Medicare, 8, 22 and patients with higher co-pays are more likely to stop treatment within the first 6 months. 8 In 2007 it was estimated that noncitizens comprise approximately 20% of the U.S. uninsured population; 23 undocumented immigrants comprise a disproportionate percentage of the uninsured, and following the Affordable Care Act (ACA) may represent up to 25% of the total uninsured population.…”
Section: Discussionmentioning
confidence: 99%
“…47 In response, since 2008 43 states and Washington D.C. have passed laws to ensure parity in cost-sharing for oral and intravenous anticancer therapies (i.e., “oral chemotherapy parity” laws). 8 These laws are intended to ensure that cost-sharing for patients (e.g., copayments, coinsurance, benefit limits) is equivalent for anticancer drugs obtained with medical (intravenous) and pharmacy (oral) benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, 62.1% of all US bankruptcies were attributable to medical reasons, even though three quarters of these patients had health insurance, and bankruptcies attributable to medical problems rose by 49.6%, compared to 2001 [6]. High patient costs have been associated with non-adherence to TKIs in multiple studies [7, 8]. …”
Section: Why Consider Stopping?mentioning
confidence: 99%